(untitled) (European Journal of Marketing and Economics, 2022)
The Sino-Egyptian smart Hackathon commune project is to endorse Dr./ Dina Ali Mohammed El-Besomey, the Primary founder - pioneer- leader(with 100%) For a post-doctoral mission under the mission Call 2022-2023. The purpose of the post-doctoral mission is applying Sino -Egyptian commune project of advertisement and distributing animation products for graduated youth. The importance of the mission is this Applied study for Future Chinese –Egyptian Electronic Education vision 2030 - 2020). This project is as scientific mission of my post- PHD. This project focuses on the contemporary Chinese animation industry, especially The Role of Demography in the Distribution of Advertising Animation Products via the Experience of Chinese Communes with smart hackathon and how to apply it in Egypt. As the Demography of Advertising Animation Products via Chinese Communes, and the impact of them on the contemporary Chinese industry. Also on another hand explain that many of the Egyptian animation companies suffer from such problems as the production reduction ,the expensive costs ,to produce animation films with high quality ,so Chinese and Egyptian companies should be concentred with the post- production stage to achieve profits . So I suggest to build this project in Damanhour,El-Behira Government, Egypt. And there is a discussion with El-Behira Government where it will be build and distribute Demography This Sino-Egyptian commune project in Damanhour, and also distribute Advertising Animation Products to the output of this project in his first stage to build one Sino-Egyptian commune to distribute his Advertising Animation Products, like: video tapes, DVD, video games, posters, stickers, comics, magazine, school tools, toys, electronic games, children clothes, masks, and interior designs.